The correlation between family function and health-promoting lifestyle among female adolescents in Iran - Naeimeh Sarkhani; Shahzad Pashaeypoor; Shima Haghani (Kashan University of Medical Sciences, 2021)
Background: Health-promoting lifestyle (HPL) is a major health concern among adolescents. Family function (FF) has potential effects on adolescents' lifestyle and health. Objectives: This study aimed to evaluate the correlation between FF and HPL among female adolescents. Methods: This correlational study was conducted from January to February 2020 on 356 female adolescent students randomly recruited through multistage cluster sampling from four public junior high schools in the south of Tehran, Iran in 2020. Data were collected using a personal characteristics questionnaire, the Adolescent Health Promotion Short Form, and the McMaster Family Assessment Device. Data analysis was performed through Pearson's correlation coefficient, the one-way analysis of variance, the independent-samples t test, and the linear regression analysis. Results: The average age of adolescents was 14.16 ± 0.76 years. The total mean scores of participants' HPL and FF were 75.36 ± 12.43 (in the possible range of 21-105) and 3.02 ± 0.37 (in the possible range of 1-4), respectively. There was a significant positive correlation between FF and HPL (r = 0.399, P < 0.001). Among demographic characteristics, adequacy of family income, and among dimensions, the problem-solving, behavioral control, roles, and affective involvement dimensions of FF were significant predictors of HPL, explaining 24.5% of its total variance. Conclusion: The mean HPL and FF were greater than the possible median scores. Also, adequacy of family income and FF were significant predictors of HPL among female adolescents. Healthcare authorities and policymakers are recommended to pay greater attention to FF in developing health-promoting programs for adolescents.